2012
DOI: 10.1002/hed.22930
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for oropharyngeal cancer treatment de‐escalation

Abstract: Patients accept little difference in survival between treatments to avoid toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 68 publications
3
33
0
3
Order By: Relevance
“…It has been shown that late dysphagia was the major correlate of decreased QoL [42], and before and after treatment patients prioritize swallowing abilities among other functional outcomes [43]. Scientific literature about patient preferences in head and neck oncology is scarce outside of larynx preservation [44] but when asked about their preferences, head and neck cancer patients ultimately prioritize survival over QoL [45]. It might be hypothesized, although this remains to be proven, that the reduction of subacute and chronic side effects observed in IMPT patients could reduce some of the costs associated with the delivery of this advanced technique [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that late dysphagia was the major correlate of decreased QoL [42], and before and after treatment patients prioritize swallowing abilities among other functional outcomes [43]. Scientific literature about patient preferences in head and neck oncology is scarce outside of larynx preservation [44] but when asked about their preferences, head and neck cancer patients ultimately prioritize survival over QoL [45]. It might be hypothesized, although this remains to be proven, that the reduction of subacute and chronic side effects observed in IMPT patients could reduce some of the costs associated with the delivery of this advanced technique [39].…”
Section: Discussionmentioning
confidence: 99%
“…When studying de‐escalation, however, it is important to re‐emphasize the need for equivalent disease control. A structured interview of advanced‐stage OPSCCA patients receiving concurrent CRT has shown that patients are only willing to accept a maximum of 5% reduction in survival to mitigate treatment‐related complications . Survival analysis of over 43,000 OPSCCA patients from 1998 to 2009 had demonstrated improved survival with surgery or CRT compared to radiation therapy alone, highlighting the ability to choose between the two with respect to overall survival (OS) outcome.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 Although the standard treatment for HPV-positive and HPV-negative oropharyngeal cancer continues to be similar, prospective trials are under way to determine whether therapy can be stratified solely on the basis of HPV status. 8–10 …”
mentioning
confidence: 99%